Trace element enrichment mechanisms in black shales during the early cambrian (ca. 521–514 Ma), South China. (March 2023) - Wang, Zhanghu; Tan, Jingqiang; Hilton, Jason; Dick, Jeffrey; Wen, Zhigang
Abstract: It is widely accepted that significant perturbations in ocean redox states are closely related to biological evolution during the early Cambrian. However, the host and geochemical cycle of redox-sensitive elements (V and Zn) of the Niutitang Formation shale in South China have not been well-constrained. This study reports lithofacies, mineralogy and geochemical data of high-resolution samples from slope and basin settings (Xa1 and Xb1 wells, Hunan Province), to evaluate the significance of redox condition and hydrothermal contribution to trace element accumulation during the early Cambrian. Our results reveal the Zn-rich host is primarily sphalerite, while the V-rich host includes organic matter, illite, and anatase minerals in the Niutitang shale. Illite and anatase minerals have significant V concentration (14.8% and 18.3%), whereas organic matter contains relatively lower V concentration (1.4%). Trace elements can be scavenged by dissolved organic matter in seawater, and then taken up by clay minerals or form sulfide during deposition/diagenesis of organic-rich shales. Although seawater restriction of the lower member (LM) shale was stronger than in the upper member (UM) shale, euxinic conditions were more conducive to V and Zn enrichment than ferruginous conditions. Specifically, dwindling concentrations of V and Zn in seawater existed in South China during deposition of the early LM shale. However, the ocean experienced episodic hydrothermal activity, which may have supplied abundant trace elements to supplement seawater content. Overall, we propose that the V and Zn geochemical cycles in the early Cambrian paleo-ocean were controlled by redox condition, organic matter, and the trace element inventory of seawater. Highlights: The hosts of V and Zn elements in organic-rich shale of Niutitang Formation have been determined. Euxinic condition was more favorable for the enrichment of trace elements relative to ferruginous condition. The seawater restriction of UM/LM shale of Niutitang Formation was investigated. V and Zn inventory in the ocean was in a drawdown trend during the early Cambrian. Hydrothermal activity may carry abundant trace elements into the ocean.